The Imaging Diagnosis of Patients with Shoulder Pain Caused by Sports Injury - Xiaoqi Dong; Lu Wang (Applied Bionics and Biomechanics)
The shoulder joint is the most complex and movable joint of the human body. A variety of diseases can affect the shoulder joint and cause shoulder pain. Sports injuries are an important and common cause of shoulder pain. In the clinical diagnosis of shoulder joint injury, the most commonly used diagnostic methods are X-ray photography and CT imaging, but X-ray photography has poor ability to distinguish shoulder joints and other tiny tissue structures and has a sense of inspiration for shoulder joint injuries. In addition, CT arthrography has a certain risk to the lesion and is easy to form trauma, and it cannot clearly show the shoulder joint structures such as the rotator cuff and the labrum. Therefore, this article conducts MR imaging diagnostic research on patients with shoulder pain caused by sports injuries and plays an important role in imaging. This article deeply studied the clinical manifestations of shoulder joint pain and image processing technology, designed a research experiment on imaging diagnosis results of patients with shoulder joint pain caused by sports injuries, selected 87 patients with shoulder joint pain in a hospital, and analyzed X-ray photography, CT imaging, and MR imaging diagnosis, three methods to compare the diagnostic accuracy and inspection results and conduct an in-depth analysis of the causes of shoulder joint injury. The experimental results showed that there were 87 patients with shoulder joint pain, 65 patients with rotator cuff tear were diagnosed using arthroscopy, and 63 patients with rotator cuff tear were diagnosed by MR imaging. The accuracy rate was as high as 95.6%. Among them, the proportion caused by sports injuries is the highest, reaching 56%.